2003
DOI: 10.1088/0953-8984/15/47/015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thin films of a-SiOx(1.1<x<2.0) prepared by reactive evaporation of SiO

Abstract: Thin films of a-SiO x with values of x ranging from 1.13 to 1.89 were prepared by reactive evaporation of SiO in a controlled oxygen environment. The oxygen pressure in the deposition chamber was varied so as to obtain films with different values of x. The films were studied by x-ray photoelectron spectroscopy and optical spectrophotometry. An attempt was made to analyse the Si 2p corelevel spectra in terms of five chemically shifted components corresponding to basic Si bonding units Si-(Si 4−n O n ) with n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…A lower density for SiO x ͑x Ͻ 2͒ compounds than that of Si and SiO 2 have been previously reported by several authors. 1,13,19,38 From the series of samples analyzed in this study, the low density in the asdeposited SiO x films proves the formation of a new phase, and discards the possibility of considering the SiO x thin films prepared here as a mixture of segregated Si and SiO 2 domains.…”
Section: E Reels Spectra Of Sio X Thin Filmsmentioning
confidence: 82%
“…A lower density for SiO x ͑x Ͻ 2͒ compounds than that of Si and SiO 2 have been previously reported by several authors. 1,13,19,38 From the series of samples analyzed in this study, the low density in the asdeposited SiO x films proves the formation of a new phase, and discards the possibility of considering the SiO x thin films prepared here as a mixture of segregated Si and SiO 2 domains.…”
Section: E Reels Spectra Of Sio X Thin Filmsmentioning
confidence: 82%
“…The first and third deconvolution peaks were identified using available reference data. 6) The second peak at $102:4 eV was assigned to Si 3þ according to the results of Durrani et al 7) They examined thin films of SiO x with values of x ranging from 1.13 to 1.89 by XPS and showed that film with x > 1:65 can include only two oxide components corresponding to Si 3þ at 102.7 eV and Si 4þ at 103.8 eV. The other authors 8) reported also that films of SiO 1:3 stoichiom- and Si 0 states, respectively.…”
Section: 3)mentioning
confidence: 99%
“…In pure silicon the binding energy of the Si 2p peak is 99.5 eV 31–35. By the binding of silicon to oxygen, the binding energy is shifted by around 1 eV per SiO bond to higher energy 32.…”
Section: Introductionmentioning
confidence: 99%
“…It is the same energy range in which the SiO bonds are localized. Also the C1s peak of carbon, which was fixed by calibration of the energy axis at 284.5 eV, does not permit a separation of SiO and SiC/H 31, 35. The CO bonds are shifted to a higher energy of 286.61 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation